PENINGKATAN SERVIS BAWAH BOLA VOLI DENGAN PENDEKATAN BERMAIN DI SDN 06 PAKUMBANG - Margareta, Margareta; Haetami, Mimi; Triansya, Andika (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
Abstract:The problem of this study: Is there an increase in service learning outcomes under volleyball using a play approach on students of class V SDN 06 Pakumbang. The purpose of this research is to know the Improved learning of volleyball service using play approach on V class student SDN 06 Pakumbang. The method of this research is classroom action research method. The subjects in this study are students class V SDN 06 Pakumbang Landak District. The total number of students of class V students is 27 students. Based on the results of the study found that the improvement of learning in the first cycle there are results mastery with the number of 12 students or by 44.4% and learners who have not completed amounted to 15 students or by 55.6%. While the second cycle there are results of learners with complete category all with graduate students amounted to 27 students or 100% and not complete 0 or none.Keywords: Service  down, Play Approach